Case Study on Effect of Aragvadhadi Ksharsutra in Management of Fistula-in-Ano - Dr. Akanksha Dasila,; Dr. Bharat Rokade,; Dr. Shelar Suvarna, (The Bioscan, 2026)
Fistula-in-ano is a chronic and recurring anorectal disorder. In Ayurveda, it is referred as Bhagandara, one of the AshtaMahagada1. In bhagandara, Apamarga Ksharsutra is traditionally used for its effective cauterizing and healing properties7, patients often experience discomfort, pain, and irritation. The present study explores the use of Aragvadhadi Ksharsutra, a formulation made from Aragvadha, Haridra, Aguru, Madhu, and Ghrita, as a less irritating, more patient- friendly alternative in the treatment of fistula-in-ano.10